Dismenorrea primaria en mujeres trabajadoras: revisión bibliográfica - Sánchez-Peña, Emely (2026)
Primary dysmenorrhea is one of the most common gynecological disorders among women of reproductive age. It is characterized by intense pelvic pain without any identifiable underlying pathology and is a frequent cause of school and work absenteeism. Despite its prevalence, there is limited scientific research on how working conditions may influence its onset or aggravation, which restricts occupational health interventions.A scientific literature review was conducted to analyze the potential relationship between primary dysmenorrhea and occupational conditions, based on an understanding of its pathophysiology and risk factors. Special attention was also given to the state of the art in Costa Rica, from both legal and scientific perspectives.The review identified physiological and hormonal factors associated with dysmenorrhea, as well as occupational risks such as stress and rotating night shifts, particularly documented among Asian nurses. A lack of research focused on working women and in regions such as Latin America was evident. In Costa Rica, no scientific studies were found addressing menstrual health in the workplace,and official reports on women’s health do not include this issue. Primary dysmenorrhea has significant implications for women’s health, well-being, and productivity.It is essential to promote local research and develop public policies that incorporate menstrual health within the framework of occupational health, aiming toward greater labor equity.